SOSIALISASI IMPLEMENTASI SISTEM KEHADIRAN KARYAWAN TERINTRAGRASI GEOTAGGING PADA PT. KOOKMIN CARD FINANSIA MULTI FINANCE - Markani Pato; Ramlah P; Nurnaningsih Nurnaningsih; Syaharullah Disa; First Wanita; Neneng Awaliah; Asnimar Asnimar; Mursalim Mursalim; Amran Amiruddin (Bajang Institute, 2023)
Employees of PT Kookmin Card Finansia Multi Finance, still uses traditional methods is fingerprint where are have various limitations and weaknesses such as making a marketing employee assigned outside the company to come to the office first to make kehadiran. This study aims to create a Geotagging Integrated Attendence System at PT Kookmin Card Finansia Multi Finance to make it easier for marketing employees to do kehadiran and documentation by providing gps access to find out the location. And the company can monitor employees on duty outside the company. The system development method used in this research is the Rapid Application Development (RAD) method. The RAD method is a system development method with a relatively short processing time. This data was obtained through, 1) Field Research, 2) Direct interviews with marketing, 3) Documentation. The system development method used in this research is the Rapid Application Development (RAD) method. The RAD method is a system development method with a relatively short processing time. Based on the test results using the UAT (User Acceptance Tens) testing technique, 84% of the 21 respondents obtained results, so it was declared feasible based on the tests carried out